Nitrogen components, growth and gas exchange in spring wheat plants grown under interaction of silicon (Si) and nitrogen (N) - da Silva, Edson Santos [UNESP]; Prado, Renato de Mello [UNESP]; dos Santos, Durvalina Maria Mathias [UNESP]; Cruz, Flávio José Rodrigues [UNESP]; de Almeida, Hilário Júnior [UNESP]; Campos, Cid Naudi Silva [UNESP] (My University, 2015)
Some studies have reported a synergistic effect between N and Si in plant growth. The effect of interaction between Si and N on the nitrogen metabolism, growth and gas exchange in spring wheat plants genotype IAC 375 was therefore investigated in the present study. Two Si doses (0 and 1.8 mmol L-1) and five N doses (1.4, 3.6, 7.1, 14.3 and 28.6 mmol L-1) were used. The concentrations of leaf (R2=0.66*) and root silicon (R2=0.24*) were influenced by the dose of 1.8 mmol L-1 of Si while unaffected by N doses. On the other hand, N doses were more decisive than Si in nitrate reductase activity, and leaf and root nitrogen content. The stomatal conductance (R2=0.91**), transpiration (R2=0.93**) and intercellular CO2 concentration (R2=0.98**) were lower in the dose of 1.8 mmol L-1 of Si, however, net photosynthesis (R2=0.98*) was higher in this Si dose. The instantaneous (R2=0.71**) and intrinsic water use efficiencies (R2=0.52**) were higher in the presence of 1.8 mmol L-1 of Si, but decreased with increasing N levels. Leaf area, shoot dry mass and root dry mass of plants grown in the presence or absence of Si were influenced by N and not by Si. Silicon was effective in improving water ratios in wheat plants, however the interaction between Si and N was not was sufficiently effective to increase N uptake and promote dry matter gains in wheat plants.
Keywords: Dry mass; Stomatal conductance; Transpiration; Triticum aestivum L; Water use efficiency